SELLING IN A CRISIS 21 ways to stay motivated, destroy your competition, and crush your number... in volatile times - BLOUNT, JEB (JOHN WILEY, 2022)
Find the motivation and confidence to stay on top when everything hits the fan In volatile times, it is hard to sell. It seems like every company is on a spending freeze, cutting back, or pushing off making decisions. Buyers become scarce and the competition for the few that are still buying is fierce. People don't want to meet with you, objections are harsher, customers cancel orders and contracts on a whim and pressure you for price decreases. Yet, you are still under the same pressure to make your sales number. If you don't, your income will take a hit. Don't even mention the 401(k) that you are afraid to even look at with the markets in free fall. In this situation, it's natural to feel stressed out and feel demotivated. In Selling in a Crisis, the world's most sought-after sales trainer Jeb Blount delivers an essential blueprint for staying motivated, keeping your pipeline full, increasing sales, retaining your customers, and advancing your career in times of uncertainty and change. In his classic, no-nonsense style, Jeb gives you 55 easy to consume tips, techniques, and tactics that are time-tested and proven to help you stay on top when everything and everyone else is down. You'll also discover: The real secrets to selling more in a crisis The difference between rainmakers and rain barrels and how to find opportunity in adversity Why you must stop swimming naked and put your bathing suit on Why you don't get into buckets with crabs How to be a RIGHT NOW sales professional 7 Steps of Effective Prospecting Sequences and how to be professionally persistent How to adjust sales messaging to meet the moment The sales secrets of frogs, squirrels, and horses Sutton's Law and why you must go where the money is Why you need more than charm and a great personality to close sales in a crisis The five questions you must answer in the affirmative for every stakeholder How to handle buying commitment objections in a crisis How to protect your turf from competitors and your profits from price decreases Five ways to protect and advancing your career How to be bold and always trust your cape And so much more . . . Jon Kabat-Zinn once said, "You can't stop the waves, but you can learn to surf." This is exactly what you'll learn to do in this indispensable guide for sales professionals who are navigating the rough seas of volatility. With each chapter you will find the motivation, inspiration, and confidence catch to rise above the negativity, catch your wave, and take control of your life, career, mindset, and income.
Keywords: Selling -- Psychological aspects; Vente; Aspect psychologique; Selling; Psychological aspects